#TITLE_ALTERNATIVE# - JANUAR GUSNAWAN (NIM : 23009025); Pembimbing : Dr Azis Trianto; Dr Sutopo, PRI
Demand for natural gas in Indonesia tends to increase with reduction in fuel subsidies, consumtion shifting from kerosene to LPG, development of petrochemical industry and environmental issues. Indonesia natural gas reserves are quite large but spread out in several areas, both onshore and offshore. To supply consumers demand, natural gas must be collected, processed, and transported. One of natural gas transporting methods is flowing through pipeline system. Natural gas pipeline can be affected by different temperature conditions that might cause condensation. A good understanding of two-phase flow behavior due to condensation in gas pipeline system by simulation method is necessary. One-phase flow model can simulate gas flow but will be inaccurate if condensation occur so it must be simulated by two-phase flow model. In this research, steady state gas flow model due to condensation and the solution methods have been arranged. The model is one-phase and two-phase couple model with phase change criteria modification. Sensitivity analysis results that environment temperature change does not effect gas velocity, pressure and temperature, as long as condensation does not occur. Environment temperature is able to cause retrograde condensation which leads to an increase of gas velocity, gas pressure and gas temperatur reduction until below environment temperature. Environment temperature which cause retrograde condensation in this research is 273 K.